1970
DOI: 10.1029/wr006i001p00310
|View full text |Cite
|
Sign up to set email alerts
|

A technique of generating a synthetic flow record to estimate the variability of dependable flows for a fixed reservoir capacity

Abstract: The variability of dependable flows for fixed storage is an important parameter that should be incorporated into the economic analysis of a water resource storage project. Flow values representative of the James River were computed by a hydrologic model that uses data randomly generated from monthly precipitation distributions. Dependable flows from fixed storage were found to have large variance. Confidence limits were placed on the dependable flows illustrating the wide range of possible dependable flows for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Based on Yevjevich (1964) they also introduced a correlation from year to year to allow for storage carry‐over and historical sequences of wetter and drier years. Colston and Wiggert (1970) developed confidence limits for dependable reservoir flows using stochastic monthly simulations, though Klemeš and Bulu (1979) later suggested that such estimates should be considered to have limited confidence. Salas and Smith (1981) show how the Thomas and Fiering model is equivalent to an autoregressive moving‐average (ARMA) model of flow and groundwater storage, with structures depending on the structure of the rainfall inputs in applying the water balance.…”
Section: Generation Of Stochastic Series Of Dischargesmentioning
confidence: 99%
“…Based on Yevjevich (1964) they also introduced a correlation from year to year to allow for storage carry‐over and historical sequences of wetter and drier years. Colston and Wiggert (1970) developed confidence limits for dependable reservoir flows using stochastic monthly simulations, though Klemeš and Bulu (1979) later suggested that such estimates should be considered to have limited confidence. Salas and Smith (1981) show how the Thomas and Fiering model is equivalent to an autoregressive moving‐average (ARMA) model of flow and groundwater storage, with structures depending on the structure of the rainfall inputs in applying the water balance.…”
Section: Generation Of Stochastic Series Of Dischargesmentioning
confidence: 99%
“…The idea of uncertainty then was actually more often referred to in relation to potential future hydrological time series as stochastic variables (e.g., for optimization of water resource management, reservoir design and flood frequency analysis). How to generate stochastic time series using Monte Carlo methods was an important area of development as digital computers became more widely available (e.g., amongst many others, Colston & Wiggert, 1970; Cowpertwait & O'Connell, 1992; Harms & Campbell, 1967; Weiss, 1977).…”
Section: Setting Off On the Walkmentioning
confidence: 99%